2011
DOI: 10.1186/1749-8090-6-147
|View full text |Cite
|
Sign up to set email alerts
|

Intra aortic balloon pump: literature review of risk factors related to complications of the intraaortic balloon pump

Abstract: The increasing use of the intra aortic balloon pump is attributed to the relatively easy percutaneous insertion and the low threshold of use over the past few years, especially in elderly patients with multi-vessel diseases and an affected ejection fraction.Unfortunately, the clinical assessment of the complications associated to the use of this supporting device, underestimates the frequency of such complications.This report has looked at the current literature and attempt to identify incremental risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 32 publications
0
36
1
2
Order By: Relevance
“…The PAxIABP complication rates were comparable to femoral IABP complications published in a literature review by Parissis. [19] New nursing care protocols, staff education on IABP console management, and intensive interdisciplinary collaboration between PT, nursing, and the patients' families were instituted in caring for these patients. More research is needed on the preoperative psychological effect on patients (anecdotal accounts from multiple patients have been very positive) and postoperative implications of this alternative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The PAxIABP complication rates were comparable to femoral IABP complications published in a literature review by Parissis. [19] New nursing care protocols, staff education on IABP console management, and intensive interdisciplinary collaboration between PT, nursing, and the patients' families were instituted in caring for these patients. More research is needed on the preoperative psychological effect on patients (anecdotal accounts from multiple patients have been very positive) and postoperative implications of this alternative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because the management of patients with ECMO is very complex, IABP might be useful as the bridging therapy until ECMO introduction. It has been reported that the IABP can improve the balance between myocardial oxygen supply and consumption, as well as improving the peripheral circulation 5, 6, 7. We suggest that the IABP is beneficial for septic cardiomyopathy patients who had decompensated heart failure with LV dysfunction because it reduces afterload, increases coronary blood flow, and also improves the coronary circulation.…”
Section: Discussionmentioning
confidence: 70%
“…We included patients with coronary disease requiring surgical treatment and LVEF less than or equal to 40%. Patients with absolute contraindication to the intra-aortic balloon, such as severe aortic insufficiency and aortic dissection, were excluded [6]- [8].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the IABP use is related to some complications, such as thromboembolism, ischemic lesions that depend, mainly, on the permanence time of the IABP and the surgeon's skill in the catheter installation [5] [6].…”
Section: Introductionmentioning
confidence: 99%